Penggunaan Debat Bahasa Inggris Untuk English as a Foreign Language Students dalam Pengajaran Speaking - Rossydi, Ahmad (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2019)
technique as a medium of teaching speaking to level II students of the CASEA Makassar to speak English. (2) find out whether the Level II cadets are interested in speaking in English through an English debate. This research uses qualitative and quantitative methods. Data was collected using observations, duration of speech, and questionnaires. The results of this study indicate that (1) the cadets of CASEA Makassar can speak English more actively through the use of debate, because in this case the debate technique was used as a teaching medium for teaching speaking. Cadets can produce more words than each meeting. The use of this debate needs to be done, so that cadets can increase their confidence, mood, interest, enthusiasm, and reduce nervousness when speaking English. And in the end it has an impact on the duration of speech and the use of vocabulary in speaking English. (2) the implementation of the debate was interesting for the cadet because it was fun, motivated them, and challenged the cadets to speak English. Of the 24 samples, 10 people were categorized into very high interested classification that is 40%, 10 people were categorized into high interest classification that is 40% and 4 people were categorized into the medium level classification.